2007
DOI: 10.1002/app.25844
|View full text |Cite
|
Sign up to set email alerts
|

Poly(methylmethacrylate)‐poly(vinyl pyrrolidone) microspheres as drug delivery systems: Indomethacin/cefadroxil loading and in vitro release study

Abstract: Poly(methylmethacrylate)-poly(vinyl pyrrolidone) (PMMA-PVP) microspheres loaded with cefadroxil (water-soluble) and indomethacin (water-insoluble) drugs have been prepared by the dispersion polymerization technique using PVP as a steric stabilizer. Microspheres have been characterized by differential scanning calorimetry (DSC), scanning electron microscopy (SEM) and X-ray diffraction (X-RD) studies. DSC studies indicated coating of PVP onto PMMA microspheres. SEM suggested the formation of microspheres in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…In some research studies, the effect of PMMA hydrophilicity on drug release from the capsules has been studied. It is found that the increasing of polymer hydrophilicity by formulating PMMA with hydrophilic polymers, improves the drug release …”
Section: Release Mechanisms Of Core From Pmma Microcapsulesmentioning
confidence: 99%
“…In some research studies, the effect of PMMA hydrophilicity on drug release from the capsules has been studied. It is found that the increasing of polymer hydrophilicity by formulating PMMA with hydrophilic polymers, improves the drug release …”
Section: Release Mechanisms Of Core From Pmma Microcapsulesmentioning
confidence: 99%
“…DSC thermograms of graft copolymers, plain NFD, placebo microspheres, NFD-loaded microspheres and NaAlg coated microspheres were all recorded on a Rheometric Scientific, Model DSC-SP, UK in the temperature range of 25-400 • C at the heating rate of 10 • C/min under an inert nitrogen atmosphere [21].…”
Section: Differential Scanning Calorimetric (Dsc) Studiesmentioning
confidence: 99%
“…50 The intensity and bandwidth of CdS fluorescent bands are related to the size and the nature of carrier trap states located at the surface of the nanocrystals. 21 An emission band broadening may be considered as an effect of the change of surface environment and the change in particle size when CdS nanocrystallites are embedded in PMMA matrix. 21 In our present experimental conditions we observed the wide yellow emission profile of all samples centered at around 540-610 nm and can be considered as surface trapped induced emission, 24 i.e.…”
Section: Steady State Photoluminescence Spectramentioning
confidence: 99%
“…17 Poly (methyl methacrylate) [PMMA] is an important polymer which has exhibited the property of biocompatibility 18,19 and it has been used for drug delivery. 20,21 We have reported the size-selective photoluminescence 22 and anomalous photocurrent behaviour 23 for PMMA-Ag nanocrystals. To study the optical and electrical properties, in our laboratory a program was taken for the preparation of CdS QDs with different capping agents, 4,[24][25][26] QDs-polymer nanocomposites 22,23 and organic-inorganic nanocomposites for application in photodetectors.…”
Section: Introductionmentioning
confidence: 99%